Analysis of Various Marketing Strategies for Wedding Organizer PT. Pratoza Kreasi Nusantara To Increase Consumer Purchase Interest - Wardi Saputra , Wardi Saputra; Tri Suratmi, Tri Suratmi; Maryati Tamba, Maryati Tamba (LPPM Universitas Respati Indonesia, 2023)
Pratoza Kreasi Nusantara is engaged in services, one of which is the Wedding Organizer